ANALISIS PERTUMBUHAN PENDUDUK TERHADAP KESENJANGAN SOSIAL DALAM PERSPEKTIF MASYARAKAT - tayudin, sujai; Maruapey, Muhamad Husein; Rusliandy, Rusliandy (Universitas Djuanda, 2022)
The purpose of this paper is to determine the impact of population growth on social disparities based on the community perspective. The method in this writing is to use qualitative methods with direct interview data collection techniques. The result of this research is that after conducting an analysis of the impact of population growth based on the perspective of the community, it can be seen that Cilengsi area is one of the areas with the largest population capacity in Bogor Regency. Thus, based on information from the community due to the density of the population but the uneven number of jobs it can only cause a problem of social inequality. There is a social problem that often occurs in cilengsi areas, namely: congestion caused by the entry and exit of industrial factory employees, the vulnerability of crime and rampant street children due to the existence of disparities in the uneven socio-economy.